Heavy flavour decay muon production at forward rapidity in proton-proton collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (ELSEVIER, 2012)
The production of muons from heavy flavour decays is measured at forward rapidity in proton-proton collisions at root s = 7 TeV collected with the ALICE experiment at the LHC. The analysis is carried out on a data sample corresponding to an integrated luminosity L-int = 16.5 nb(-1). The transverse momentum and rapidity differential production cross sections of muons from heavy flavour decays are measured in the rapidity range 2.5 < y <4, over the transverse momentum range 2 < p(t) < 12 GeV/c. The results are compared to predictions based on perturbative QCD calculations. (C) 2012 CERN. Published by Elsevier B.V. All rights reserved.
Keywords: LHC; ALICE experiment; pp collisions; Single muons; Heavy flavour production; PRODUCTION CROSS-SECTION; BOTTOM-QUARK PRODUCTION; P(P)OVER-BAR COLLISIONS; HADRON-COLLISIONS; J/PSI PRODUCTION; ALICE; Astronomy & Astrophysics; Physics